Pengembangan Model Artificial Intelligence Capability terhadap Kinerja Rumah Sakit melalui Transformasi Digital dan Inovasi Pelayanan Kesehatan - Ratih Purwasih; Ade Saputra (Jurnal Sains Informatika Terapan, 2026)
Artificial Intelligence (AI) has emerged as a strategic technology capable of transforming healthcare services and improving organizational performance. Despite increasing investments in AI technologies, limited research has explored how AI capabilities contribute to hospital performance through digital transformation and service innovation. This study aims to develop an integrated model that examines the relationship between Artificial Intelligence capability, digital transformation, healthcare service innovation, patient satisfaction, and hospital performance. The proposed framework assumes that AI capability enhances digital transformation initiatives, which subsequently foster service innovation and improve patient satisfaction, ultimately leading to better organizational performance. A quantitative approach will be adopted through a survey involving healthcare professionals, hospital managers, and information technology personnel from various hospitals. Data will be analyzed using Structural Equation Modeling (SEM) to assess the direct and indirect relationships among the proposed constructs. The expected results will provide empirical evidence regarding the strategic role of AI in enhancing healthcare service quality and organizational outcomes. The findings are expected to contribute to the literature on digital healthcare transformation and offer practical recommendations for hospital leaders in leveraging AI technologies to achieve sustainable competitive advantages.